2003
DOI: 10.1021/bi034968u
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Rate of Reduction of Oxyferrous Cytochrome P450 2B4 by 5-Deazariboflavin Adenine Dinucleotide T491V Cytochrome P450 Reductase

Abstract: The use of 5-deazaFAD T491V cytochrome P450 reductase has made it possible to directly measure the rate of electron transfer to microsomal oxyferrous cytochrome (cyt) P450 2B4. In this reductase the FMN moiety can be reduced to the hydroquinone, FMNH(2), while the 5-deazaFAD moiety remains oxidized [Zhang, H., et al. (2003) Biochemistry 42, 6804-6813]. The rate of electron transfer from 5-deazaFAD cyt P450 reductase to oxyferrous cyt P450 was determined by rapidly mixing the ferrous cyt P450-2-electron-reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
69
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 39 publications
(62 reference statements)
7
69
0
Order By: Relevance
“…However, the lack of any significant change in the rate of the first electron transfer observed in the absence of benzphetamine suggests that any modulation in the redox potential is relatively insignificant with respect to its effect on the electron transfer rate. The substantial increase in the rate of the electron transfer to the unmodified protein in the presence of 1 mM benzphetamine can be attributed to an increase in the redox potential of P450 2B4, given that it has been reported that benzphetamine binding to P450 2B4 raises the redox potential by ϳ85 mV, leading to a ϳ10-fold increase in the rate of the electron transfer from CPR to the ferric P450 2B4 (Zhang et al, 2003). This substantial stimulation of the rate of electron transfer is absent for the tBPA-modified P450 2B4.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of any significant change in the rate of the first electron transfer observed in the absence of benzphetamine suggests that any modulation in the redox potential is relatively insignificant with respect to its effect on the electron transfer rate. The substantial increase in the rate of the electron transfer to the unmodified protein in the presence of 1 mM benzphetamine can be attributed to an increase in the redox potential of P450 2B4, given that it has been reported that benzphetamine binding to P450 2B4 raises the redox potential by ϳ85 mV, leading to a ϳ10-fold increase in the rate of the electron transfer from CPR to the ferric P450 2B4 (Zhang et al, 2003). This substantial stimulation of the rate of electron transfer is absent for the tBPA-modified P450 2B4.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of product formation was measured in a rapid chemical quench apparatus by mixing a 1:1 complex of the preformed dithionite reduced Fe 2ϩ cyt P450:2-electron reduced ⌬TGEE with oxygen (49,28). The reaction was quenched, and the product was quantified by high-pressure liquid chromatography-mass spectrometry.…”
Section: Two-electron Reduced ⌬Tgee Catalyzes Product Formation By Cymentioning
confidence: 99%
“…The reduction of cyt P450 by the 2-residue deletion mutant was slightly slower than that of wild-type (6.7 s Ϫ1 versus 4.2 s Ϫ1 , Table 4) and occurred with a rate constant similar to the rate of electron transfer from FAD to FMN. Cyt P450 reduction was faster in the presence of benzphetamine, because the substrate raises the redox potential of the heme, which increases the thermodynamic driving force of the reaction (49). Fig.…”
mentioning
confidence: 94%
“…The slower oxidation of cyt P450-CO by ferric cyt b 5 may result from the increased redox potential of cyt P450-CO or the slow dissociation of CO from cyt P450-CO and subsequent reduction of cyt b 5 by ferrous cyt P450. It has been estimated that the binding of CO to ferrous cyt P450 raises the mid-point potential by Х180 mV versus NHE (36) relative to the ferric-ferrous couple in the presence of 1 mM benzphetamine (Х Ϫ245 mV versus NHE) (37). Increasing the potential would reduce the driving force for electron transfer compared with the ferrous protein.…”
mentioning
confidence: 99%